VISUAL FRAMING OF THE PROTEST AGAINST THE DICTATORSHIP - Krstić, Aleksandra; Milojević, Ana; Kleut, Jelena (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
This paper builds on the framing theory and its paradigm related to media coverage of protests. Protests are considered as multidimensional phenomena with important visual manifestations both at the time they take place and in later treatment in the media. The aim of this research was to contribute to understanding of visual framing of protests in Serbian media. For that purpose, we analyzed “Against the dictatorship” protest held after presidential elections in 2017. Our analysis was focused on TV news aired on RTS1, B92, Pink and N1, photographs published in print outlets Kurir, Informer, Vecernje novosti, Politika and Danas, and photos from web sites blic.rs and telegraf.rs. The method of content analysis was used to examine the representation of visual frames of violence, performance, legitimization and delegitimization, and social semiotics to analyze the content of frames. Results of our study show that the mediascape in Serbia is divided between outlets which positively represent protests and others which frequently use negative frames of violence and delegitimization. More than other frames, visual performance is linked with newsrooms’ work routines and focuses on the visual attractiveness of the event, while legitimization and delegitimization frames reflect political bias and editorial policies of certain media outlets.
Keywords: protest; media frames; visua framing; protest paradigm; Serbia